Laser Line Detection with Sub-Pixel Accuracy - Molder, A.; Martens, O.; Saar, T.; Land, R. (Elektronika ir Elektrotechnika, 2014)
Due to the fact that the image sensors have a fixed resolution and pixel size – a lot of image processing algorithms are limited with pixel resolution. One of those image processing algorithms is related to 3D laser scanners and in particularly to the laser line detection from images. This pixel quantization resolution, however, in many cases is not sufficient and greatly limits the laser scanner precision. In particularly the problem is highlighted in the linearly growing or declining surfaces, but also in strait lines where the actual laser line centre position is between two pixels. In this paper two laser line centre position detection methods with sub-pixel accuracy have been proposed and investigated. The methods have been tested on real images and as seen from the results at the end of the paper, the methods greatly improve the laser line detection accuracy and resolution. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7114